Pengembangan Modul Cetak Pada Mata Pelajaran Produktif Teknik Komputer Dan Jaringan Di SMK Negeri 2 Watampone - Muldiyana, Muldiyana; Ibrahim, Nurdin; Muslim, Suyitno (JTP - Jurnal Teknologi Pendidikan, 2018)
This study aims to produce a product in the form of Printing Module and Networking Printing Productive Computer for students of class X SMK. The research methodology uses R & D method. The model used is Derek Rowntree model which consists of three stages: planning, preparation of writing, writing and editing. The product testing phase begins with the validation of several material experts and media experts. Validation results by experts show the average test of material experts obtained 4.74 and media experts obtained 4.3, means the print module products are feasible and very well used. The next product tested to a number of students of class X with small group stage that is 3 respondents with face-to-face method get the overall average value 3,48, and large group trial 25 respondents with field evaluation test method obtained an average value of 4, 2 Conclusion Print module productive subjects of computer engineering and network SMK Negeri 2 Watampone good and feasible to use.Keywords: Development Research, Crane Rowntree Model, Printed material, Printed media and module Computer Asissted Instruction (CAI).